Aplicación del proceso enfermero a la práctica asistencial en el caso clínico de trauma craneoencefálico. - Cabrera Marchena, Dennys Patricio (2014)
The aim of the NANDA International, is to strengthen the development of nursing knowledge. In the present study , the steps of the nursing process is applied from assessment using the 11 Functional Health Patterns Marjory Gordon , the diagnosis was established using the NANDA International taxonomy and NOC linkage and NIC that guided the identification and implementation nursing actions . The study was prospective, descriptive qualitative. The methodology was applied to a case in an 11 -year-old, who entered the service of Pediatrics Medical Diagnosis with mild craniocerebral trauma. Such analysis, Nursing Diagnoses NANDA I: Deterioration of ambulation related to impaired balance expressed by , impaired ability to walk the distances required (Code 00088 ), Discomfort associated with anxiety manifested by lack of control of the situation (Code 00214 ), Risk for situational low self-esteem related to body image disorder ( code 00153 ), Risk of parental impairment related to lack of resources (Code 00057 ), the results correspond to NOC: Mobility (Code 0208), Control of symptoms ( Code 1608 ), Personal Resilience (Code 1309 ), Coping with family problems (Code 2600), same as directed nursing actions. Finally according to the assessment of the results by the Likert scale, the indicator is at risk: Mobility (Code 0208) with a risk of "substantially engaged" in two of its literals (running, jumping). KEYWORDS Family, Nursing process, Head injury, NANDA, NIC, NOC, User